THE QUALITY OF STEAM-PjBL MIND MAPPING SKILLS FOR PROSEPECTIVE ELEMENTARY SCHOOL TEACHERS - Muskania, Ricka Tesi; Kartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study seeks to evaluate the quality of mind mapping generated by prospective elementary school teachers within the framework of project-based learning utilizing the STEAM (Science, Technology, Engineering, Arts, and Mathematics) methodology. Mind mapping serves as a technique to illustrate students' comprehension and concepts in the development of interdisciplinary learning projects. The evaluation emphasizes four primary aspects: the precision of interdisciplinary integration, the appropriateness of the project, the novelty of the concept, and the clarity of the visualization. This study employs a descriptive qualitative methodology, utilizing documentation and content analysis tools to examine students' mind mapping outputs following their engagement in STEAM-PjBL learning. The study's results show that most participants successfully integrated multiple scientific disciplines; however, they identified deficiencies in concept originality and visualization clarity. These findings offer significant insights into prospective instructors' preparedness to create interdisciplinary learning and establish a basis for enhancing future training methodologies.